The Concept Of Children's Education In The Al-Qur'an Letter Luqman Verse 13 From Perspective Tafsir Al-Misbah - Khoirul , Muhammad (STAI Tebing Tinggi Deli, 2023)
The results of the study found that children's education in the family from the perspective of the interpretation of Al Mishbah by M. Quraish Shihab in the Qur'an Surah Luqman verses 13-15 is to provide an important role for families, especially parents, in educating children (starting at an early age) both in terms of ethics, the environment, especially in terms of monotheism (not associating partners with Allah), do good to both parents, do good to parents unless they command things that lead to polytheism, do not do lies, never lie, are not arrogant and behave politely (noble character). This also encourages the creation of human resources who instill the education of children in families in Indonesia. The concept of children's education in Surah Luqman verses 12-15 according to the thought of M. Quraish Shihab includes three concepts, namely monotheism education or creed, moral education and worship education. Children's education according to Ahmad Mustafa al-Maraghi in Tafsir al-Maraghi, namely parents must be able to provide good education to their children, especially in praying, where prayer is a pillar of Islam that must be done and can be a sin if left behind, and do what ma'ruf and prevent evil that occurs on this earth, then must be patient in dealing with problems and difficulties. To children, parents should advise not to give up easily in the face of all kinds of difficulties, but must always pray to Allah for a good way out. In this way, parents can expand their children's hearts so that their minds are not stuck, as well as educate them to look for good alternatives in solving problems with clear minds and open hearts.